The Effect of Liquidity, Leverage, Operating Capacity, Profitability, and Sales Growth as Predictors of Financial Distress : (Property, Real Estate, and Construction Services Companies Listed on the IDX) - Agil Krisna Rivanda; Kurnia Fajar Afgani; Radia Purbayati; Marziana Madah Marzuki (Journal Integration of Management Studies, 2023)
This paper begins with analyzing financial ratios by examining the effect of liquidity, leverage, operating capacity, profitability, and sales growth as predictors of firms' financial distress risk. The study employs a statistical method (logit model). Using 38 property, real estate, and construction services firms listed on the Indonesia Stock Exchange between 2016 and 2022, 646 observations were collected and analyzed using logistic regression. The results show that leverage, operating capacity, and profitability positively and significantly influenced predicting financial distress risk, while liquidity and sales growth do not affect predicting financial distress risk. The result of model calcification accuracy is 84%; this shows that the model can accurately predict the financial distress risk of property, real estate, and construction services companies in the study period of 543 observations from 646 observations or 84%. This study concludes that profitability, leverage, and operating capacity influence the financial distress risk on property, real estate, and construction services companies.